1997
DOI: 10.1152/jappl.1997.82.1.144
|View full text |Cite
|
Sign up to set email alerts
|

Effects of muscle kinematics on surface EMG amplitude and frequency during fatiguing dynamic contractions

Abstract: Fifteen male subjects performed a repetitive elbow flexion/extension task with a 7-kg mass until exhaustion. Average joint angle, angular velocity, and biceps brachii surface electromyographic (EMG) amplitude (aEMG) and mean power frequency (MPF) were calculated with each consecutive 250-ms segment of data during the entire trial. Data were separated into concentric or eccentric phases and into seven 20 degree-ranges from 0 to 140 degrees of elbow flexion. A regression analysis was used to estimate the rested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
88
1
9

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(112 citation statements)
references
References 35 publications
6
88
1
9
Order By: Relevance
“…They concluded/suggested that the EMG data (iEMG and MDF) obtained during isometric and isotonic contractions of the muscles are similar 31) . Frequency spectrum analysis under dynamic conditions have also been investigated during repeated eccentric-concentric muscle contractions of plantar flexors in patients with stroke 32) , in the upper esophageal sphincter-opening muscles during head lift exercise 33) in healthy elderly subjects, and in the biceps brachii of normal young male subjects 34) . Therefore, in our study the frequency spectrum analysis for muscle fatigue was also performed under dynamic conditions during walking.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded/suggested that the EMG data (iEMG and MDF) obtained during isometric and isotonic contractions of the muscles are similar 31) . Frequency spectrum analysis under dynamic conditions have also been investigated during repeated eccentric-concentric muscle contractions of plantar flexors in patients with stroke 32) , in the upper esophageal sphincter-opening muscles during head lift exercise 33) in healthy elderly subjects, and in the biceps brachii of normal young male subjects 34) . Therefore, in our study the frequency spectrum analysis for muscle fatigue was also performed under dynamic conditions during walking.…”
Section: Discussionmentioning
confidence: 99%
“…Time domain features such as Mean Absolute Value (MAV), number of Zero Crossings (ZC), number of Slope Sign Changes (SSC) and Waveform Length (WL), average EMG amplitude (aEMG), variance (VAR) and Root Mean Square (RMS) were considered for pattern recognition [35,36,37,38]. These features were extracted from 4 channels of sEMG signals during the sketching of each shape.…”
Section: Feature Extractionmentioning
confidence: 99%
“…Regra geral, durante um exercício submáximo com predominância de contracções isométricas verifica-se um aumento dos componentes do sinal EMG no domínio do tempo, enquanto as características no domínio da frequência do sinal se deslocam para zonas de baixa frequência (para refs. ver 69,75,95,119) . Tem sido proposto que a resposta dos músculos à fadiga, durante um exercício submáximo, se traduz num aumento do número de unidades motoras recrutadas e/ou na sua sincronização, de forma a compensar a redução da capacidade de gerar força pelas unidades motoras e que esta resposta é responsável pelo aumento da amplitude do sinal EMG (para refs.…”
Section: Modelos De Estudounclassified
“…A compressão do espectro EMG, ou seja, o desvio da frequência de mediana e de média (Hz) para as zonas de baixa frequência durante a fadiga muscular, parece ser influenciado, predominantemente, pela diminuição da velocidade de condução do potencial de acção (para refs. ver 95,119) , em consequência, pelo menos em parte, do aumento da concentrações de ácido láctico durante o exercício e consequente diminuição do pH (71) . Embora a determinação dos componentes do sinal electromiográfico no domínio da frequência seja, habitualmente, efectuada durante a realização de contracções isométricas, diversos estudos têm, recentemente, tentado avaliar estes componentes, assim como os do domínio do tempo, em exercícios dinâmicos, normalmente, realizados em dinamóme-tros isocinéticos, quer no modo concêntrico, quer excêntrico (62,68,71,95) .…”
Section: Modelos De Estudounclassified